PENGARUH KESAKRALAN DAN PLACENESS TERHADAP KEPUASAN BERKUNJUNG DENGAN PERCEIVED VALUE SEBAGAI VARIABEL MEDIASI PADA PENGUNJUNG UPACARA SEKATEN YOGYAKARTA - Santoso, Aurelia Angelica; Oktavio, Adrie (ITB AAS Indonesia Surakarta, 2024)
The purpose of this study is to examine the influence of experiential festivals on visitor satisfaction at Sekaten Yogyakarta ceremony with perceived value as a mediating variable. The population of this study is tourists who have visited Sekaten Yogyakarta ceremony for the last two years and a sample of 150 domestic tourists was obtained. Data collection was carried out by distributing questionnaires using the Likert scale through Google Forms. Moreover, the method used in this study is quantitative analysis with a Structural Equation Model (SEM) which was processed by the Smart-PLS software. The variables of this study are festival experience consisting of sacredness and placeness as the independent variables, visiting satisfaction as the dependent variable, and perceived value as the mediating variable. Furthermore, the examination was executed on seven hypotheses which was found that sacredness and placeness affect perceived value positively and significantly. In addition, perceived value has a positive and significant effect on visiting satisfaction. In addition, sacredness and placeness have positive and significant effects on visiting satisfaction hence perceived value partially mediates between festival experience, which are sacredness and placeness, and visiting satisfaction.